The Effect of Number of Visits, Use of Solvent and Gutta-percha Removal Technique on Postoperative Pain following Nonsurgical Endodontic Retreatment; A Systematic Review and Meta-analysis: Pain after endodontic retreatment - Lima Scardini, Iandara; Sarra, Giovanna; Braga, Mariana; dos Santos, Marcelo; Freire, Laila (Iranian Endodontic Journal, 2023)
Introduction: The nonsurgical endodontic retreatment (NERT) is the first choice of dental ministration when primary/initial endodontic treatment fails. The present study aimed to investigate the presence of postoperative pain (POP) after NERT in permanent asymptomatic teeth as well as possible factors associated with POP. Materials and Methods: A comprehensive search of literature was performed in Pubmed/MEDLINE, Embase, Scopus and Web of Science databases, up to January 2023; including randomized clinical trials and prospective studies. The risk of bias was assessed with RoB 2.0 and ROBINS-I tools. Subgroups analyses were conducted to evaluate the differences in the incidence or level of POP between the number of visits, the use/not use of solvent, the removal technique of gutta-percha, and the period of POP analysis. Mean differences and confidence intervals (CI) of 95% were used as measures of effect, and meta‐regression was used along with subgroup analysis. The certainty of evidence was assessed using GRADE, and the probability value of <0.05 was considered significant. Results: Twenty-four studies were selected, with thirteen included in the meta-analysis. There was a statistical difference between the incidence of POP after 24 h (95% CI, 0.28 to 0.52) and one week (95% CI, 0.02 to 0.13) from the endodontic retreatment (P<0.01). However, there was no statistical difference between different techniques, number of visits and use of solvent (P>0.05) in the same period. In addition, the certainty of evidence was very low. Conclusions: Post-operative pain is a common response to NERT, independent of the retreatment technique(s) applied, number of visits and use of solvent(s); with very low certainty of evidence as well as low risk of bias. Moreover, the current analysis showed a (very) serious risk of inconsistency and imprecision. However, POP was significantly reduced within 1 week of the NERT.